STRUKTUR HISTOLOGIS HEPAR, INTESTINUM, DAN REN BURUNG CEREK JAWA (Charadrius javanicus Chasen 1938) YANG TERKONTAMINASI DDT DI PANTAI TRISIK KULON PROGO YOGYAKARTA - , DEWI PUSPITA SARI; , Prof. Dr. Istriyati, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Residues of DDT (Dichloro Diphenyl Trichloroethane) in the coastal environment can get into the Bird's body through an intermediary Java Plover natural feed. Residues of DDT will experience biomagnification and biotransformation in the body organism. The purpose of this research was to determine residue of DDT in the Trisik Coast region, several organs of birds, and their impact on liver, intestine, and kidney Javan Plover. This research was located in Progoâs downstream and Trisikâs coastal. Sampling was conducted in June- July 2011. The method of environment and feed sampling done directly on site. The bird sampling using mist nets. Detection of residues DDT in environment samples by gas chromatography. Measurement of DDT residues in feed and organs of birds with spectrophotometer. Preparation of histological slide from liver, intestine, and kidney using paraffin method (with Hematoxylin & Eosin and Mallory Acid Fuchsin staining). Quantitative Data obtained from the measurement results of environment, feed, and organs of Javan Plover samples. Qualitative data analize by descriptively. The analysis showed DDT residues detected in areaâs Progo downstream, Trisik coast, natural feed and Javan ploverâs organ exceeds the threshold environmental quality standards. Analysis shows chronic effects posed by DDT residue on the histological structure of liver, intestine, and kidney Javan Plover.